Screening of Drug Interaction Prescreption for Outpatients with Diabetes Mellitus and Hypertension from October to December 2023 at Advent Hospital Medan - Khairatunawa, Tisa; Bangar, Roy Indrianto (NSMRJ: Nusantara Scientific Medical Research Journal, 2025)
Diabetes mellitus and hypertension are two chronic conditions that frequently occur simultaneously and require long-term pharmacological therapy. The combination of treatments in patients with both diseases increases the potential for drug interactions, which can compromise therapeutic effectiveness and elevate the risk of adverse effects. This study aimed to evaluate the severity of drug interactions in outpatients with diabetes mellitus and hypertension at Advent Hospital Medan during the period from October to December 2023. A non-experimental descriptive study with a cross-sectional design was employed, using retrospective data from 191 outpatient prescriptions that met the inclusion criteria. Evaluation was conducted on administrative, pharmaceutical, and clinical aspects of the prescriptions, with a primary focus on identifying drug interactions using the reference database Drugs.com. The results showed that drug interactions were present in 52.4% of the analyzed prescriptions. Most interactions were classified as moderate in severity, predominantly involving pharmacodynamic mechanisms. The most frequent interacting drug combinations included metformin, glimepiride, amlodipine, bisoprolol, and candesartan. The high prevalence of drug interactions among patients with diabetes mellitus and hypertension highlights the importance of systematic prescription screening as a preventive measure. These findings can serve as a basis for developing rational drug use policies and enhancing patient safety in clinical practice.